1990
DOI: 10.1182/blood.v75.8.1711.1711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sickle cell membranes

Abstract: The mechanical properties of sickle erythrocyte membranes were evaluated in the ektacytometer. When ghosts from the total red blood cell population were examined, the rigidity of the resealed ghosts and their rate of fragmentation by shear stress (t1/2) were normal. However, fractionation on Stractan density gradients revealed that sickle cells were heterogenous in their membrane mechanical properties. The ghosts from dense cell fractions exhibited both increased rigidity and decreased stability. Presumably, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Sickle RBCs are mechanically fragile, and dense sickle RBCs are particularly susceptible to mechanical damage, probably because of decreased membrane stability . Because patients with SS and α‐thalassemia have decreased numbers of dense cells, it is likely that their RBCs are less mechanically fragile.…”
Section: Discussionmentioning
confidence: 99%
“…Sickle RBCs are mechanically fragile, and dense sickle RBCs are particularly susceptible to mechanical damage, probably because of decreased membrane stability . Because patients with SS and α‐thalassemia have decreased numbers of dense cells, it is likely that their RBCs are less mechanically fragile.…”
Section: Discussionmentioning
confidence: 99%
“…They found that cellular dehydration and the consequent increase in cytoplasmic viscosity are major determinants of the abnormal rheologic behavior of oxygenated sickle cell anemia RBC. Studies on resealed ghosts showed that membrane changes of sickle cell anemia RBC, such as altered material properties, increased extensional rigidity, and decreased membrane stability (53,89), contribute to the abnormal deformability of sickle cell anemia RBC.…”
Section: Determinants Of Blood Rheology and Rbc Microrheologymentioning
confidence: 99%
“…For example, in patients with sickle cell disease 125 (BOX 1), mutated haemoglobin polymerizes in low oxygen conditions leading to an increase in cell stiffness and reduced deformability. In addition, as the red cell continuously travels between low and high oxygen concentrations, the fluctuating mechanical loads to the membrane applied by polymerizing haemoglobin contribute to the aforementioned haemolysis 126 . Similarly, in the early stages of malaria infection, red blood cells that contain the parasite become stiffer 127,128 and more adhesive, allowing them to stick to the wall of small blood vessels and evade detection by the immune system 129 .…”
Section: Mechanical Properties Of Red Blood Cellsmentioning
confidence: 99%
“…Effect on haemostasis and the immune system-A change in the collective cell number may also impair haemostatic function 126,132 . For example, abnormally high numbers of white blood cells can lead to leukostasis, a medical condition in which cells block blood flow, which can cause a transient ischemic attack and a stroke 143 .…”
Section: Emergent Properties Of the Blood Cell Collectivementioning
confidence: 99%